Examining the self-efficacy of teacher candidates' lifelong learning key competences and educational technology standards - Kan, Ayse Ulku; Murat, Aysel (Springer, 2020)
The aim of this study is to examine the relationship between the candidate's lifelong learning key competences and educational technology standards self-efficacy. Relational scanning model was used in the study. The sample of the study consists of 594 teacher candidates enrolled in the pedagogical formation course of the Faculty of Education of Firat University. In order to collect data, the Lifelong Learning Key Competences Scale developed by Sahin, Akbasli and Yanpar-Yelken (2010) and Competences Scale for Educational Technology Standards developed by coklar (2008) were used. Diagnostic analysis, t-test, MWU and Pearson Correlation analysis were benefited from for data analysis. According to the analyzes, it was determined that teacher candidates participated in lifelong learning key competencies in upper intermediate level in dimensions other than communication in foreign language competence sub-dimension. Significant results were found in favor of female candidates in terms of the competence of communication in the mother tongue, competency to learn learning, competency of social citizenship awareness and according to the gender variable across the scale. It is determined that teacher candidates have high level of educational technology standards self-efficacy. A significant difference in favor of female candidates was observed according to the gender variable technological processes and concepts knowledge, and according to gender learning environments and planning and designing of learning experiences sub-dimensions. It was figured out that teacher candidates had moderate level positive relationships between the key competences of lifelong learning and the educational technology standards self-efficacy sub-dimensions. In the light of the results of the research, it has been recommended some suggestions.
Keywords: Lifelong learning; Educational technology standards; Competence; Teacher candidate